SGLT-2 inhibitors in patients with and without a history of heart failure: a meta-analysis. (14th October 2021) - Razuk, V; Chiarito, M; Cao, D; Nicolas, J; Camaj, A; Power, D; Beerkens, F; Tavenier, A.H; Pivato, C; Mehran, R; Dangas, G
Abstract: Background: Sodium-glucose co-transporter 2 (SGLT-2) inhibitors emerged as a new groundbreaking therapy for patients with heart failure. Recent evidence showed significant benefits in patients with heart failure with reduced ejection fraction (HFrEF), regardless of diabetic status. Whether these medications also improve outcomes in patients without a history of heart failure or with heart failure with preserved ejection fraction (HFpEF) remains unknown. Purpose: We sought to perform an updated meta-analysis of randomized controlled trials to evaluate the effects of SGLT-2 inhibitors on cardiovascular (CV) outcomes according to the history and type of heart failure. Methods: All randomized, placebo-controlled trials of SGLT-2 inhibitors reporting similar CV outcomes were evaluated for inclusion. PubMed was searched from January 1, 2010 to February 1, 2021. Articles were independently reviewed and selected by two reviewers. The primary outcome was the composite of first hospitalization for heart failure and CV death. Secondary outcomes included its single components and all-cause mortality. Pooled hazard ratios (HR) and 95% confidence intervals (CI) were used as effect estimates and calculated with a random-effects model. Heterogeneity was assessed with the I 2 index, and random-effects meta-regression was used to assess the interaction between treatment effect and history of heart failure and type of heart failure (HFrEF vs. HFpEF). Results: Data from eight trials and a total of 56, 665 patients (n=31, 609 in SGLT-2 group, n=25, 056 in placebo group) were included. Five studies enrolled high-risk patients with diabetes mellitus, while 3 studies enrolled patients with symptomatic heart failure. SGLT-2 inhibitors reduced the risk of first hospitalization for heart failure and CV death in patients with (HR 0.75 95% CI 0.70–0.81) and without (HR 0.78 95% CI 0.67–0.90; Figure 1) a history of heart failure. Similarly, patients with (HR 0.85 95% CI 0.78–0.93) or without (HR 0.85 95% CI 0.74–0.98) a history of heart failure treated with SGLT-2 inhibitors had a significant reduction in all-cause mortality. SGLT-2 inhibitors reduced the risk of CV death regardless of the history of heart failure, although the reduction was border-line statistically significant in patients without a history of heart failure (HR 0.81 95% CI 0.66–1.00; Figure 2). All subgroup interaction testing between patients with and without a history of heart failure was negative for all the above endpoints. Among patients with HFpEF, SGLT-2 inhibitors were associated with a nonsignificant trend towards reduced risk of the primary outcome (HR 0.80 95% CI 0.63–1.02). Conclusions: SGLT-2 inhibitors significantly improve CV outcomes in patients with or without history of heart failure, and this effect seems to be consistent among those with HFrEF and HFpEF. Funding Acknowledgement: Type of funding sources: None.